2020
DOI: 10.21053/ceo.2019.00556
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Low-Cost and Simple Simulator for Microlaryngeal Surgery

Abstract: Objectives. The simulation of microlaryngeal skills is rarely seen in surgical training, but it is particularly important in phonomicrosurgery. This study described and validated the laryngeal surgical simulator through surgical training.Methods. A simple and low-cost simulator was developed for the fixation of the suspension laryngoscope and porcine larynges. Twenty participants with work skills and experience did preparation before training, and performed suture and carbon dioxide (CO2) laser cordectomy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In the literature, there are different proposals for laryngeal microsurgery training models: synthetic, ex vivo, or mixed models. Twenty phonomicrosurgery reports with simulation models were found (research date: March 31, 2022) (Table 4), 8/20 had face validity, 6,15,30‐35 8/20 had content validity, 1,2,6,31,33,36‐38 and 6/20 had construct validity, 1,2,30,34,37,39 6/20 were not validated 8,40‐44 . Predictive validity was not assessed in any simulation program.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, there are different proposals for laryngeal microsurgery training models: synthetic, ex vivo, or mixed models. Twenty phonomicrosurgery reports with simulation models were found (research date: March 31, 2022) (Table 4), 8/20 had face validity, 6,15,30‐35 8/20 had content validity, 1,2,6,31,33,36‐38 and 6/20 had construct validity, 1,2,30,34,37,39 6/20 were not validated 8,40‐44 . Predictive validity was not assessed in any simulation program.…”
Section: Resultsmentioning
confidence: 99%
“…They report that experts had significantly higher scores than novices who performed: VF nodule excision and keratosis excision, 30 VF injection and tissue preservation, 1 and suture and CO 2 laser cordectomy. 37 Fleming et al report significantly higher scores in SRS for the expert group compared to novices but no difference in the GRS scores. 34 In the present study, we found significant differences between the expert and resident groups in both SRS and GRS, with higher scores for the experts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation